Hubungan Antara Efikasi Diri dan Kematangan Karier Ditinjau dari Gender sebagai Moderator pada Siswa Kelas XII SMK Negeri di Kecamatan Semarang Selatan - Galuh Prastika Guritno; Maria Theresia Sri Hartati; Achmad Miftachul 'Ilmi (Journal of Innovative and Creativity, 2025)
The high unemployment rate among vocational high school (SMK) graduates is partly due to low work readiness, which is associated with a lack of career maturity. Many students experience confusion in determining their career direction, lack confidence in their abilities, and do not yet have a clear career plan. This study aims to examine the relationship between self-efficacy and career maturity, with gender as a moderating variable, among 12th-grade students of public vocational high schools in the South Semarang District. The research uses a quantitative method with a correlational moderator design. The sample consisted of 267 students selected through stratified random sampling from five public vocational schools in Semarang. Data were collected using psychological scale instruments to measure self-efficacy and career maturity, both of which had high validity and reliability. Data analysis was conducted using moderated regression with PROCESS Macro Model 1 in SPSS 26. The results showed that self-efficacy had a positive and significant effect (R² = 0.548, p < 0.001) on career maturity, contributing 54.8%. All three dimensions of self-efficacy—magnitude, generality, and strength—had a significant effect, with the strength dimension being the strongest predictor at 51.8%. The moderating effect occurred in the female gender subpopulation (t = 4.5439; p = 0.000 < 0.05; LLCI = 0.5369; ULCI = 1.3581). These findings highlight the importance of enhancing self-efficacy to support students' career readiness, especially among female students. Additionally, school counselors can design guidance and counseling programs that positively influence self-efficacy and thereby impact students' career readiness. Further research can explore in more depth the relationship between self-efficacy and male students in improving career readiness.